Influence of the climate variability and two mineral fertilization programs on nitrogen losses in coffee (Coffea arabica L.) - Ramirez-Builes, Victor Hugo; Villegas, Andres Mauricio; Agudelo, Miguel Angel; Sotelo, Juan Camilo; Moriano, Kelly; Junklewitz, Petra (Frontiers in Environmental Science, 2025)
IntroductionGlobal coffee production is increasingly vulnerable to climate change and variability, particularly nitrogen (N) losses via ammonia volatilization (NH3) and nitrate (NO3−) leaching. Improved N management could mitigate these losses, yet field-level evidence under ENSO-driven climate variability remains limited. We aimed to quantify N losses via leaching and volatilization under two contrasting fertilization programs in a Colombian coffee plantation and assess their sensitivity to El Niño/La Niña-Southern Oscillation (ENSO) phases.MethodsA field experiment was conducted from 2022 to 2024 in the Central West coffee region of Colombia. N leaching was monitored using drainage lysimeters, and NH3 volatilization was measured with semi-open static collectors. This study spanned two ENSO phases La Niña (2022–mid-2023) and El Niño (mid-2023–2024). Two fertilization programs were evaluated: a urea-based NPK blend (UB-NPK), an ammonium-nitrate-based NPK (ANB-NPK), and a no-N control.ResultsNitrogen losses were significantly influenced by both fertilizer type and climate phase. During La Niña (negative ENSO phase), leaching was dominant loss pathway, with no significant differences between treatments. During El Niño (positive ENSO phase), NH3 volatilization became the dominant loss mechanism, with significantly higher losses in the UB-NPK treatment. Cumulatively, after 2 years and six fertilizations, mean N losses were 36.7% for UB-NPK and 13.1% for ANB-NPK of the total N applied.DiscussionENSO-driven climate variability alters nitrogen loss dynamics in coffee systems. Urea-based fertilizers resulted in greater losses under El Niño conditions, while ammonium-nitrate-based blends showed improved N retention. These findings highlight the potential of fertilizer type selection as a mitigation strategy under variable climate conditions.